Applications of computational fluid dynamics to congenital heart diseases: a practical review for cardiovascular professionals. (3rd October 2021) - Rigatelli, Gianluca; Chiastra, Claudio; Pennati, Giancarlo; Dubini, Gabriele; Migliavacca, Francesco; Zuin, Marco
ABSTRACT: Introduction: The increased survival rate of patients with congenital heart disease (CHD) has made it likely that 70%–95% of infants with CHDs surviving into adulthood often require careful follow-up and (repeat) interventions. Patients with CHDs often have abnormal blood flow patterns, due to both primary cardiac defect and the consequent surgical or endovascular repair. Area covered: Computational fluid dynamics (CFD) alone or coupled with advanced imaging tools can assess blood flow patterns of CHDs to both understand their pathophysiology and anticipate the results of surgical or interventional repair. Expert opinion: CFD is a mathematical technique that quantifies and describes the characteristics of fluid flow using the laws of physics. Through dedicated software based on virtual reconstruction and simulation and patients' real data coming from computed tomography, magnetic resonance imaging, and 3/4 D-ultrasound, reconstruction of models of circulation of most CHD can be accomplished. CFD can provide insights about the pathophysiology of coronary artery anomalies, interatrial shunts, coarctation of the aorta and aortic bicuspid valve, tetralogy of Fallot and univentricular heart, with the capability in some cases of simulating different types of surgical or interventional repair and tailoring the treatment on the basis of these findings.